Oral lesions in patients with severe COVID-19 in the National Institute of Respiratory Diseases in Mexico: Case series - Carlos Alberto Carrasco Rueda; Ilan Vinitzky Brener (Tabriz University of Medical Sciences, 2023)
Oral manifestations in patients with COVID-19 have already been reported in the literature. Determining whether the oral manifestations in these cases are directly related to SARS-CoV-2 infection or not has been challenging for both clinicians and researchers, although at present it has not been possible to prove. There are several possible causes for the development of the oral lesions in patients with COVID-19, among them are, opportunistic infections, drug reactions, iatrogenic and those directly related to viral infection. The present work describes the main characteristics of 10 severe COVID-19 hospitalized patients with oral manifestations. By analyzing the characteristics of the reported patients, and what is published in the literature, we conclude that for this series of cases the manifestations are not directly related to SARS-CoV-2, however, it is a possibility that should be considered for all patients.